Food Promotion and Children's Health: Considering Best Practices for Teaching and Evaluating Media Literacy on Food Marketing - Elliott, Charlene; Truman, Emily; Nelson, Michelle R.; Scheibe, Cyndy; Hudders, Liselot; De Jans, Steffi; Brisson-Boivin, Kara; McAleese, Samantha; Johnson, Matthew; Walker, Lauren; Ellison, Kirsten (Frontiers in Public Health, 2022)
Food marketing to children is ubiquitous and persuasive. It primarily promotes foods of poor nutritional quality, influences children's food preferences and habits, and is a factor in childhood obesity. Given that food marketing relentlessly targets children in traditional/digital media and the built environment, children need critical media literacy skills that build their understanding of food marketing's persuasive effects. However, little research connects media literacy with food marketing and health, including effective strategies for teaching and evaluating such programming for children. This perspective presents the outcomes of a stakeholder meeting on best practices in teaching and evaluation on media literacy and food marketing to children. Strategies for promoting critical thinking (teaching content, teaching practices, teaching supports, and parent/caregiver involvement), and strategies for measuring critical thinking (program effectiveness and broader long-term impacts) were identified. These include, among other things, the need to capture the range of marketing formats and current food promotion trends, to include inquiry-based and co-creation activities, and to support ongoing media literacy development. Overall, these strategies suggest useful criteria for media literacy programming related to food marketing, and highlight the importance of media literacy for giving children the skills to navigate a complex food environment.